Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
2x + 3y < -3 ⇒ 2x + 3y = -3 ⇒ 2x + 3y = -3
-4x + y ≥ 2 ⇒ -4x + y = 2 ⇒ -12x + 3y = 6
-14x = -9
-14 -14
x = ⁹/₁₄
2x + 3y = -3
2(⁹/₁₄) + 3y = -3
1²/₇ + 3y = -3
- 1²/₇ - 1²/₇
3y = -4²/₇
3 3
y = -1³/₇
The solution set is {(⁹/₁₄, -1³/₇)}.
-4x + y ≥ 2 ⇒ -4x + y = 2 ⇒ -12x + 3y = 6
-14x = -9
-14 -14
x = ⁹/₁₄
2x + 3y = -3
2(⁹/₁₄) + 3y = -3
1²/₇ + 3y = -3
- 1²/₇ - 1²/₇
3y = -4²/₇
3 3
y = -1³/₇
The solution set is {(⁹/₁₄, -1³/₇)}.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.